Glare prediction and mechanism of adaptation following implantation of hydrophilic and hydrophobic intraocular lenses - Bhogal-Bhamra, Gurpreet K.; Aujla, Maana; Kolli, Sai; Sheppard, Amy L.; Wolffsohn, James S. (Frontiers in Ophthalmology, 2024)
PurposeGlare is a known side effect of intraocular lens (IOL) implantation, affected principally by IOL material and optics, although it is reported subjectively to decrease in impact with time. However, little objective data have been published on changes over time, how these relate to subjective reports, and whether those who will report greater glare symptoms can be predicted prior to IOL implantation.MethodsA total of 32 patients (aged 72.4 ± 8.0 years) with healthy eyes were implanted bilaterally with hydrophilic 600s (Rayner, Worthing, UK) or hydrophobic Acrysof (Alcon, Texas, USA) acrylic IOLs (n = 16 each, randomly assigned). Each patient reported their dysphotopsia symptoms subjectively using the validated forced choice photographic questionnaire for photic phenomena, and halo size resulting from a bright light in a dark environment was quantified objectively in eight orientations using the Aston Halometer. Assessment was performed binocularly pre-operatively and at 1, 2, 3, and 4 weeks after IOL implantation.SettingThe study was carried out at the National Health Service Ophthalmology Department, Queen Elizabeth Hospital, Birmingham, UK.ResultsVisual acuity (average 0.37 ± 0.26 logMAR) did not correlate with subjective glare (r = 0.184, p = 0.494) or objective glare (r = 0.294, p = 0.270) pre-surgery. Objective halo size (F = 112.781, p < 0.001) decreased with cataract removal and IOL implantation and continued to decreased over the month after surgery. Subjective dysphotopsia complaints (p < 0.001) were also greater pre-surgery, but did not change thereafter (p = 0.228). In neither case was there a difference with IOL material (p > 0.05). It was not possible to predict post-surgery dysphotopsia from symptoms or a ratio of symptoms to halo size pre-surgery (p > 0.05).ConclusionsSubjective dysphotopsia and objective halos caused by cataracts are greatly reduced by implantation of IOL after cataract removal causing few perceivable symptoms. However, objective measures are able to quantify a further reduction in light scatter over the first month post-IOL implantation, suggesting that any subjective effects over this period are due to the healing process and not due to neuroadaptation.